Standardisasi Parameter Spesifik dan Nonspesifik Ekstrak Etanol Daun Kelor (Moringa oleifera) Asal Kabupaten Blora - Marcus Yudhi Purwoko; Syamsudin Syamsudin; Partomuan Simanjuntak (FAKULTAS FARMASI, INSTITUT SAINS DAN TEKNOLOGI NASIONAL, 2020)
Moringa oleifera leaves are plants commonly consumed by peoples in Indonesia. These leaves are believed to cure several diseases including improving memory and learning functions in children. The purpose of this study was to obtain standardization of extracts using two parameters, namely specific parameters and nonspecific parameters. Specific parameters including water-soluble chemical compounds and ethanol, while nonspecific parameters including loss of drying, moisture content, ash content, and heavy metal contamination. The process begins with macerating the extraction of Moringa leaves using 96% ethanol solvent, then evaporated with a rotary evaporator and freeze-drying to obtain a stable extract in storage. The results of the specific parameters test, namely water-soluble chemical compounds of 12.54%, and the ethanol-soluble compounds of 50.21%, The result of nonspecific parameters testing showed that the loss of drying was 8.48%, water content was 8.08%, ash content was 5.61%, heavy metal contamination with Hg was not detected, As was not detected, Pb was 24.80 ppm, Cd was not detected, and the yeast mold rate is negative. The results of testing for specific parameters meet the standards, while the result of testing for nonspecific parameters does not meet the standards of the Ministry of Health RI 2000, with the presence of heavy metal Pb contamination.